Lung microbiome of stable and exacerbated COPD patients in Tshwane, South Africa - Goolam Mahomed, T.; Peters, R. P. H.; Allam, M.; Ismail, A.; Mtshali, S.; Goolam Mahomed, A.; Ueckermann, V.; Kock, M. M.; Ehlers, M. M. (Scientific reports, 2021)
Chronic obstructive pulmonary disease (COPD) is characterised by the occurrence of exacerbations triggered by infections. The aim of this study was to determine the composition of the lung microbiome and lung virome in patients with COPD in an African setting and to compare their composition between the stable and exacerbated states. Twenty-four adult COPD patients were recruited from three hospitals. Sputum was collected and bacterial DNA was extracted. Targeted metagenomics was performed to determine the microbiome composition. Viral DNA and RNA were extracted from selected samples followed by cDNA conversion. Shotgun metagenomics sequencing was performed on pooled DNA and RNA. The most abundant phyla across all samples were Firmicutes and Proteobacteria . The following genera were most prevalent: Haemophilus and Streptococcus . There were no considerable differences for alpha and beta diversity measures between the disease states. However, a difference in the abundances between disease states was observed for: (i) Serratia (3% lower abundance in exacerbated state), (ii) Granulicatella (2.2% higher abundance in exacerbated state), (iii) Haemophilus (5.7% higher abundance in exacerbated state) and (iv) Veillonella (2.5% higher abundance in exacerbated state) . Virome analysis showed a high abundance of the BeAn 58058 virus, a member of the Poxviridae family, in all six samples (90% to 94%) . This study is among the first to report lung microbiome composition in COPD patients from Africa. In this small sample set, no differences in alpha or beta diversity between stable and exacerbated disease state was observed, but an unexpectedly high frequency of BeAn 58058 virus was observed. These observations highlight the need for further research of the lung microbiome of COPD patients in African settings.